Rescue endoscopic bleeding control for nonvariceal upper gastrointestinal hemorrhage using clipping and detachable snaring - Lee, J. H.; Kim, B. K.; Seol, D. C.; Byun, S. J.; Park, K. H.; Sung, I. K.; Park, H. S.; Shim, C. S. (Endoscopy, 2013)
Nonvariceal upper gastrointestinal (UGI) bleeding recurs after appropriate endoscopic therapy in 10 % – 15 % of cases. The mortality rate can be as high as 25 % when bleeding recurs, but there is no consensus about the best modality for endoscopic re-treatment. The aim of this study was to evaluate clipping and detachable snaring (CDS) for rescue endoscopic control of nonvariceal UGI hemorrhage. We report a case series of seven patients from a Korean tertiary center who underwent endoscopic hemostasis using the combined method of detachable snares with hemoclips. The success rate of endoscopic hemostasis with CDS was 86 %: six of the seven patients who had experienced primary endoscopic treatment failure or recurrent bleeding after endoscopic hemostasis were treated successfully. In conclusion, rescue endoscopic bleeding control by means of CDS is an option for controlling nonvariceal UGI bleeding when no other method of endoscopic treatment for recurrent bleeding and primary hemostatic failure is possible.